This Pengembangan Media Poster Keanekaragaman Vegetasi Hutan Desa Genduang Kecamatan Pangkalan Lesung Untuk Pembelajaran Biologi SMA - Noviani, Riska; Sri Wulandari; Resma Wahyuni (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to determine the diversity of vegetation found in the Genduang Village Forest area, Pangkalan Lesung District, and integrated into the design of poster media on biodiversity material. This study is a type of quantitative descriptive research consisting of 2 stages, namely the field research stage in the Genduang Village Forest, Pangkalan Lesung District, Pelalawan Regency and the poster media design stage. Determination of the research location was carried out by purposive sampling, which means that the determination of the station used as a research site is based on certain considerations, namely high vegetation density, medium density and low density so that 3 research stations were obtained. The parameters observed include biological parameters and environmental physical and chemical parameters. The results of this study are the composition of vegetation in the Genduang Village Forest found as many as 16 families with tree strata consisting of 223 individuals, pole strata consisting of 145 individuals, sapling strata consisting of 94 individuals and seedling strata consisting of 259 individuals. The diversity index value for tree strata is 2.255 categorized as moderate, pole strata is 1.998 categorized as moderate, sapling strata is 1.949 categorized as moderate, and seedling strata is 1.621 categorized as moderate. Chemical factors are soil pH ranging from 6.7–7.0. Physical factors are soil temperature ranging from 26.67-280C, air temperature ranging from 27.50-290C and air humidity ranging from 83.41-90%. The results of the vegetation diversity index in the Genduang Village forest are categorized as moderate diversity. The results of the research that has been conducted are integrated into the design of poster media on biodiversity material in grade X of high school which can later be used in the biology learning process in schools.